Mercado de rochas ornamentais no âmbito do arranjo produtivo de base mineral - Alves, Márcio Henrique (2021)
The present study, in the format of a collection of articles, has as an objective to present a research based in the production arrangement of the mineral sector. Research was conducted about the ornamental rock market in the state of Goiás, Brazil, sugesting improvements through data analysis, pointing weaknesses and strenghts in the Goiás ornamental rock sector. The research also compreends the moment experienced by the sector during the period of the first semester of the year 2020, moment in wich the world was surprised by the Covid-19 pandemic. Another analysis presented, based on existing data, are the results of petrography and technological characterization of an ultramilonite, known as “Green Galaxy”, used as dimension stone, and found in the city of Marco, in the Ceará state, Brazil. The productive arrangement of the mineral sector has multiple permanent challenges and bottlenecks in its evolution, and the research shows characteristics and contributions to the study and applications of a sector that lack a wider and more effective scientific approach.